Rumo a um novo marco regulatório para o gás natural - Lucia Helena Salgado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The essay intends to emphasize the importance of a regulatory framework for the natural gas industry in Brazil. For this purpose, it is initially expounded the reasons to regulate the infrastructure network system, and presented the essential mechanisms to its efficient exercise. Through the data presentation regarding consumption per sector, it is ighlighted the relevance of natural gas in Brazil and its potential demand. Finally, the essay analyses the Proposed Law n. 6.673/2006, whose final edition indicates solutions to several obstacles to the industry's expansion.
Keywords: K23; L95; N76; Q38; 330